Application of Drill Method to Improve Starting Technique and Learning Results of 100 Meter Running Speed in Elementary School Students - Lubis, Fadhil Ammar Rizqillah; Akbar, M. Ghozali Aufathul; Tampubolon, Eka Selvia (Jurnal Inovasi Olahraga, 2025)
Purpose of the study: This research aimed to investigate the effectiveness of drill method training on improving starting technique and 100-meter running performance among elementary school students at SD Negeri 064006 in Medan City. Materials and Methods: A quasi-experimental study was conducted with 60 elementary school students (ages 10-12 years) randomly assigned to experimental (n=30) and control (n=30) groups. The experimental group received 8 weeks of structured drill method training focusing on starting technique, while the control group followed conventional physical education instruction. Pre- and post-intervention measurements included starting reaction time, 30-meter split time, and total 100-meter sprint time. Results: Significant improvements were observed in the experimental group compared to the control group. Starting reaction time improved from 0.65±0.12s to 0.48±0.09s (p<0.001), 30-meter split time decreased from 6.8±0.7s to 5.9±0.5s (p<0.001), and 100-meter total time reduced from 18.2±1.4s to 16.1±1.1s (p<0.001). The control group showed minimal improvements (p>0.05). Conclusions: The drill method training significantly enhanced starting technique and 100-meter running performance in elementary school students. This structured approach can be effectively implemented in physical education curricula to improve fundamental movement skills and athletic performance.